Mirzā Ġālib - Prigarina, Natalʹja Ilʹinična (Idāra-i Adabiyāt-i Urdū, 1997)
Life and works of Mirza Asadullah Khan Ghalib, 1797-1869, Urdu and Persian poet
Tansliterationsvariante: Mirzā G̱ẖālib
Keywords: Biografie; Ghalib; Mirza Asadullah Khan; Poets; Urdu; Poets; Persian